Lines in Water : Religious Boundaries in South Asia - Kent, Eliza F., 1966-; Kassam, Tazim R. (Book collections on Project MUSE., 2013)
This collection examines the projections and fantasies, conflict and cooperation, and borrowing and purifying that takes place around religious boundaries in South Asia and in the South Asian diaspora. These essays illustrate how people negotiate social divisions constructed on the basis of religious differences by describing, defining, maintaining, and blurring those religious boundaries in diverse ways.